How to make a school safe for students? - Teofilus Ardian Hopeman (Eastasouth Institute, 2023)
The sense of security and comfort expected at school is considered less felt by every student. Some things that cause discomfort are bullying, peer victimization, gangs in schools, school violence, and brawls between students. The students hope that the chosen school can provide a sense of comfort to guarantee a good education.